An Overview on Foreign Language Learners’ Individual Differences - Rezig, Nadia (Sciences humaines; Vol. 30 (2013): SCIENCES HUMAINES)
The foreign language teaching learning process had been subject to extensive research that aimed basically at finding out causes of failure in learning a foreign langauge.         In the twenty first century studies began to consider that thesecauses can not be limited to the teaching methods since learners present a sum of aspects among them  we can cite : prior knowledge, psychological, social, biological and cognitive abilities hich are all at work  in the learning process.        In the present paper, we’ll give an overview of foreign language learners individual differences and their different classifications.